Editorial: how safe is it to administer the BCG vaccination to babies exposed to anti‐TNFα medications antenatally?. Issue 11 (10th November 2019) - Bouri, Sonia; Hart, Ailsa L.
Abstract : LINKED CONTENT This article is linked to Luu et al papers. To view these articles, visit https://doi.org/10.1111/apt.15504 and https://doi.org/10.1111/apt.15559 .